CO BUDE, AŽ NÁDRAŽÍ NEBUDE? - Jálová, Kateřina (Vysoké učení technické v Brně. Fakulta architektury, 2024)
Diplomová práce vychází z předdiplomového projektu, který se zabývá uvolněnými objekty po odsunutí železnice z centra Brna do nově navržené polohy dopravního uzlu podle studie KAM. Diplomový projekt se zaměřuje konkrétně na památkově chráněnou výpravní budovu hlavního brněnského nádraží. Cílem je nalézt vhodnou funkci pro tuto budovu a začlenit ji do kontextu mezi historickým centrem a nově vybudovanou jižní čtvrtí. Návrh řeší i okolí objektu, do kterého spadá plocha uvolněného kolejiště a předprostor nádraží se složitou dopravní situací, který už mnoho let patří k nejméně oblíbeným veřejným prostorům ve městě.

The diploma thesis is based on the pre-diploma project, which deals with the vacant buildings after the railway is moved from the center of Brno to the newly proposed location of the transport hub according to the KAM study. The diploma project focuses specifically on the heritage-listed building of the Brno main railway station. The aim is to find a suitable function for this building and to integrate it into the context between the historic center and the newly built southern quarter. The proposal also solves the building's surroundings, which include the area of the vacant railway track and the station forecourt with its complex traffic situation, which has been one of the least popular public spaces in the city for many years.
HOW TO MOVE ON WHEN THE STATION IS GONE?
Keywords: Konverze; Nádraží; Brno; Muzeum; Památková ochrana; Park; Železnice; Rekonstrukce; Veřejný prostor; Conversion; Railway Station; Brno; Museum; Conservation; Park; Railway; Reconstruction; Public space